SRS prioritization and time-shift transmit mechanism based sidelink radio interface synchronization scheme - Xiaoyong ZHOU; Bin SHEN; Lang XU; Xiaoge HUANG (Dianxin kexue)
For LTE-V2X system,acquiring the synchronization reference signal (SRS) is indispensable for vehicles to establish service connections in the network.However,there are some vehicles may not obtain the SRS and consequently fail to be synchronized with the network.In order to solve this problem,a sidelink (SL) radio interface synchronization scheme was proposed.Vehicles select an optimal SPS according to SRS priority division mechanism.The SRS are given different priorities,where the priorities of different synchronization sources can be distinguished in a time-shift based SRS transmit mechanism and meanwhile the interference among the SRS of different sources can be effectively suppressed.Simulation results illustrate that even when the synchronization source is assigned a priority of four,the synchronization error can still be satisfied the requirement.Compared with the conventional synchronization schemes,the proposed scheme supports an expanded synchronization range aided by synchronization over the SL and achieves mitigation of SRS interference with the time-shift based SRS transmit mechanism.The proposed scheme can serve as an efficacious and feasible solution for the LTE-V2X system.